(untitled) (Palíndromo, 2026)
The study investigates how two works by Alain Huck reconfigure the relationship between nature, matter, and writing by mobilizing procedures that render the agency of materials visible. Methodologically, it combines a formal and material analysis of the works with theoretical frameworks drawn from Bennett and Derrida, in order to understand how processes of deposition, incision, and containment establish specific modes of legibility. The results indicate that charcoal, vegetal matter, plastic, and light operate as agents of inscription, producing regimes of trace, wound, and postponement that challenge both the representational model and the celebratory vitality attributed to new materialism. The study concludes that Huck develops a material form of writing that displaces the Longinian sublime by transforming visual grandeur into an experience of opacity, instability, and residual memory, thus proposing aesthetics grounded in the persistence of remains and the suspension of transparency.